YOUNG GENERATION’S PERCEPTION OF SMALL-TOWN DEVELOPMENT IN THE LAST TEN YEARS IN KALIANDA DISTRICT SOUTH LAMPUNG REGENCY - Ratu Nabillah (Tunas Geografi, 2021)
The dichotomy of "village" and "city" that often occurs in development practice requires attention to the relationship between villages and cities. This linkage can be seen in the transitional area between rural and urban areas. The transition area is a small-town. A large number of small cities in Indonesia and the significant function of the existence of small towns make the development of small towns need attention. This study aims to analyze the perceptions of the younger generation on the development of small towns in Kalianda District, South Lampung Regency, and to analyze the relationship between the identity of the young generation against various indicators of small-town development. The variables in this study are divided into the economy, education, transportation, tourism, and other developments where there are various indicators of small-town development. Percentage Analysis and Chi-Square Analysis were used in the study. This study indicates that overall the younger generation has different views on the development of small towns, but 10 out of 16 indicators are considered to be in good development (stage 2). There are only three identities of respondents who have no relationship to small – town development: gender – tourism development, social media – market development, social media – tertiary employment development.